Strategi Pengembangan Bisnis Jasa Makeover sebagai Penunjang Penampilan - Bagus Alam Mahendra; Fatimah Dzahra; Risa Resdiani; Hasim (Jurnalika : Jurnal Ilmu Komunikasi, 2026)
The makeover service business has evolved into a solution for individuals who need professional assistance in enhancing their appearance and self-confidence, particularly for important occasions such as dates. This research aims to analyze the makeover service business concept that integrates effective business communication with comprehensive appearance consultation services. The method used is literature review and conceptual analysis of business communication strategies in the makeover service industry. The analysis results show that personal, empathetic, and two-way business communication is the key to success in building trust and customer satisfaction. The services offered include style consultation, professional makeup, outfit selection, hair styling, and education on proper dating etiquette. Through a holistic approach that combines aesthetic and psychological aspects, this business provides significant added value with a target market of individuals aged 18-40 years who need professional preparation for dates. Marketing communication strategies through social media, content marketing, and word of mouth have proven effective in reaching the target market. SWOT analysis shows unique concepts and comprehensive services as the main strengths, although facing challenges in niche market segmentation. In conclusion, the integration of effective business communication with quality makeover services creates a sustainable business model with strong differentiation in the beauty service market.